Furthering the Understanding of Parent–Child Relationships: A Nursing Scholarship Review Series. Part 1: Introduction - Lutz, Kristin F. (2009)
PURPOSE: Understanding the parent–child relationship is fundamental to nursing of children and families. The purpose of this integrative review is to explore nursing scholarship published from 1980–2008 concerning parent–child relationships. Study approaches are examined, critiqued, and future directions for research identified. CONCLUSIONS: A historical review of nursing research is presented and methods described as an introduction to a review series of the parent–child relationship. IMPLICATIONS: Definition and explication of the parent–child relationship is a first-step in understanding factors amenable to nursing intervention. A clear definition of the concept of parent–child relationship will support further study using appropriate theoretical frameworks, and enable development and testing of supportive nursing interventions.